Rising : the amazing story of Christianity's resurrection in the global south - Daughrity, Dyron B., 1973- (Project Muse, 2018)
Pundits regularly declare that Christianity is dying. Its golden age of influence is long gone in Western Europe, and similar trends are happening in North America. But while it slowly dies in the West, Christianity has been coming to life in Asia, Africa, and Latin America. Now immigrants, refugees, and missionaries from the Global South bring their vibrant faith to our shores. They are bringing the gospel back to us in new and surprising ways. Christianity is rising, you just have to look around.